2014
DOI: 10.1159/000357737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Intravitreal Bevacizumab Injection on Contrast Sensitivity and Macular Thickness in Eyes with Macular Edema from Central Retinal Vein Occlusion: A Prospective, Nonrandomized, Three-Month Follow-Up Study

Abstract: Purpose: To evaluate the results of intravitreal bevacizumab (IVB) injection on contrast sensitivity (CS), best-corrected visual acuity (BCVA), foveal thickness (FT) and macular volume (MV) as measured by optical coherence tomography in patients with macular edema (ME) from central retinal vein occlusion (CRVO). Methods: Sixteen consecutive eyes from 16 patients with ME from unilateral CRVO were treated with a single IVB injection. The CS, BCVA, FT and MV measurements were obtained before the treatment and 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…To better assess visual function in AMD, various alternative metrics of functional outcome have been investigated, including dark adaptation [11], microperimetry [12][13][14], multifocal ERG [15], photo-stress recovery time [16], cone-mediated flicker sensitivity [17], photopic or scotopic light sensitivity [18,19], the Moorfields Acuity Charts [20] and contrast sensitivity [21][22][23]. Among these, contrast sensitivity (1) seems to correlate better with subjective visual impairment and visionrelated quality of life compared to VA [24][25][26][27], (2) may be affected earlier in the course of neurodegenerative disorders [28][29][30] and (3) may detect more subtle changes in visual function [24,31,32]. Contrast sensitivity quantifies the lightness or darkness needed to identify a target against its background.…”
Section: The Value Of Contrast Sensitivity Testing In Amdmentioning
confidence: 99%
“…To better assess visual function in AMD, various alternative metrics of functional outcome have been investigated, including dark adaptation [11], microperimetry [12][13][14], multifocal ERG [15], photo-stress recovery time [16], cone-mediated flicker sensitivity [17], photopic or scotopic light sensitivity [18,19], the Moorfields Acuity Charts [20] and contrast sensitivity [21][22][23]. Among these, contrast sensitivity (1) seems to correlate better with subjective visual impairment and visionrelated quality of life compared to VA [24][25][26][27], (2) may be affected earlier in the course of neurodegenerative disorders [28][29][30] and (3) may detect more subtle changes in visual function [24,31,32]. Contrast sensitivity quantifies the lightness or darkness needed to identify a target against its background.…”
Section: The Value Of Contrast Sensitivity Testing In Amdmentioning
confidence: 99%
“…[ 83 ] CS testing allows measurement of the patient's ability to see low contrast patterns and provides additional information on visual function. [ 84 85 ] In particular, CS may be a better predictor of performance in tasks requiring distance judgment of real targets, night driving, and mobility than conventional VA. CS is closely linked with both orientation and mobility, and, in patients with macular disease, may be markedly reduced despite near-normal distance VA.[ 86 ] The CS of each patient's affected eye was measured using the commercially available Pelli-Robson chart (Clement Clarke Inc., Harlow, UK), VCTS 6500 chart (Vistech Consultants Incorporation, Dayton, Ohio, USA), Chroma test (City University, London, UK), and Functional Acuity Contrast Test (FACT) chart (Stereo Optical, Inc., Chicago, IL., USA).…”
Section: Resultsmentioning
confidence: 99%
“…Because CS is dominated by retina function, increases in this functional assessment may reflect the recovery of retinal function after treatment. [ 87 ] As a result, clinical protocols including CS testing have been used to evaluate the effect of anti-VEGF treatment and showed the variable anti-VEGF treatment strategies lead to improvement in CS in patients with wet AMD,[ 51 77 83 88 89 ] ME from RVO[ 84 90 ] and DMR,[ 59 85 ] and polypoidal choroidal vasculopathy (PCV). [ 87 ] [ Table 4 ] Randomized clinical trials demonstrated that intravitreal anti-VEGF therapy could initiate a larger increase in CS than conventional laser treatment in patients with DMR.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Further, CS has been shown to be impaired earlier in the course of neurodegenerative ocular pathologies when VA is still unaffected, 7,21 the latter often underestimating the onset and/or severity of visual impairment. [36][37][38] Using the 25-item National Eye Institute Visual Function Questionnaire in patients with RRD, 39 Okamoto et al reported vision-related quality of life to be significantly correlated with postoperative CS measured by preprinted letter charts, yet no correlation was found between vision-related quality of life and postoperative VA. 40 Several previous reports have shown reduced CS in patients with RRD using preprinted letter charts. [41][42][43] Despite measuring CS using methods with poor range and resolution for sampling target contrast and frequency [28][29][30] and poor test-retest reliability, 29,31,32 those reports demonstrated the detrimental effect of RD on CS.…”
Section: Discussionmentioning
confidence: 99%
“…CS has been shown to be impaired earlier in the course of neurodegenerative ocular pathologies when VA is still unaffected, 7,23 whereas VA has been shown to often underestimate the onset and/or severity of visual impairment. [36][37][38] In our subgroup analysis of the 15 macula-off RRD eyes with BCVA better than or equal to 20/30, the mean CSF was significantly reduced compared with fellow eyes (P ¼ .02) and controls (P ¼ .045).…”
Section: Discussionmentioning
confidence: 99%